2020
DOI: 10.1108/itpd-04-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Does foreign direct investment influence manufacturing sector growth in Middle East and North African region?

Abstract: PurposeThis study empirically assessed the influence of foreign direct investment on the manufacturing sector growth in the Middle East and North African region using panel data of 18 countries covering the period of 1975–2017.Design/methodology/approachThe study employed Levin et al. (2002) test (LLC) and Im et al. (2003) panel unit root test. Furthermore, Kao’s cointegration test was applied to examine the long-run relationship between the variables. Both the Dynamic OLS and Fully modified OLS were used in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
12
0
2
Order By: Relevance
“…This result is in parallel with the literature (Sade, et al, 2021). Accordingly, it shows that if the value of the domestic currency decreases compared to the foreign currency, exports become cheaper and imports become more expensive, and thus domestic manufacturing companies will be encouraged to produce more for export and will always increase their productivity (Azolibe, 2020).…”
Section: Model and Resultsmentioning
confidence: 99%
“…This result is in parallel with the literature (Sade, et al, 2021). Accordingly, it shows that if the value of the domestic currency decreases compared to the foreign currency, exports become cheaper and imports become more expensive, and thus domestic manufacturing companies will be encouraged to produce more for export and will always increase their productivity (Azolibe, 2020).…”
Section: Model and Resultsmentioning
confidence: 99%
“…FDI in the manufacturing sector played a significant role in the transformation of developing countries, such as South Korea, Hong Kong, Singapore, and Taiwan, into developed nations. Research conducted in both developed and developing countries worldwide has revealed a diverse correlation between FDI and growth in the manufacturing sector (Azolibe, 2021). For example, Patience (2011) discovered that FDI contributed to the expansion of West Africa's manufacturing output, while Azolibe (2021) found no significant nexus between manufacturing sector growth and FDI.…”
Section: Foreign Direct Investment and The Medium And High-tech Manuf...mentioning
confidence: 99%
“…But if MNCs import intermediate goods from the home country or send output for further value addition, it releases positive impact on the home country’s economic condition. Azolibe (2020) emphasized on effects of FDI on growth of manufacturing sector of 18 countries, which include countries of all income levels from the Middle East and North African region over the period of 1975–2017. The study supports the viewpoint that vertical OFDI from a country has long-term positive impact on the growth of the manufacturing sector and recommended formulation of policies to promote IFDI and OFDI.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The impact of OFDI on the economic growth differs from country to country, depending upon investing motives (Azolibe, 2020). It can be positive or negative or may not have any effect at all.…”
Section: Literature Backgroundmentioning
confidence: 99%